Analysis Customer Relationship Orientation and Sustainability Marketing: The Mediating Role of Co-Creation Value in MSMEs - Arlin Ferlina Mochamad Trenggana; Arlin Ferlina Mochmad Trenggana; Ratih Hurriyati; Mokh Adib Sultan; Hilda Monoarfa (Dinasti International Journal of Education Management and Social Science, 2026)
Growing pressure to adopt sustainable business practices has not been accompanied by comparable progress among Micro and Small Enterprises (MSMEs), despite high levels of digital adoption. This gap highlights the need to understand how customer-oriented relational strategies can be translated into concrete sustainability marketing practices. This study examines the effect of Customer Relationship Orientation (CRO) on Sustainability Marketing across the Product Lifecycle (SMLC), with Co-Creation Value (CCV) serving as a mediating mechanism.A quantitative causal survey was conducted involving 168 Food and Beverage MSMEs in West Java, selected through purposive sampling based on active digital marketing usage and business maturity. Data were collected between July 2024 and April 2025 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The findings reveal that CRO significantly enhances Co-Creation Value, which in turn strengthens sustainability marketing practices across the product lifecycle. However, CRO does not directly influence sustainability marketing outcomes, confirming the presence of full mediation. These results demonstrate that relational orientation alone is insufficient to generate sustainability impact unless activated through collaborative value-creation processes. Co-Creation Value functions as a strategic mechanism that enables resource-constrained MSMEs to convert relational strength into practical sustainability initiatives, including environmentally responsible packaging and improved waste management. This study clarifies the relational mechanism through which customer orientation supports life-cycle-based sustainability marketing in resource-constrained MSMEs.